Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/pon.3264
|View full text |Cite
|
Sign up to set email alerts
|

Conveying genomic recurrence risk estimates to patients with early‐stage breast cancer: oncologist perspectives

Abstract: Objective-The development and increased use of genomic profiling has led to refinement of breast cancer treatment. This study sought to examine medical and surgical oncologists' perceptions of factors related to the translation and integration of Oncotype DX ® into routine clinical care.Methods-Twenty oncologists (10 medical and 10 surgical oncologists) participated in qualitative interviews. Questions centered on the following themes: oncologists' perceptions about the clinical utility of testing, the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Their opinions of the evidence appeared to affect their views of gep test results in decision-making, with several oncologists using test results as one piece of a larger puzzle rather than relying more heavily on the results, as was the case for other oncologists. Our findings are similar to those of Spellman et al 28 , who found that oncologists were concerned that too much weight was given to test results rather than to other clinical data.…”
Section: Discussionsupporting
confidence: 81%
“…Their opinions of the evidence appeared to affect their views of gep test results in decision-making, with several oncologists using test results as one piece of a larger puzzle rather than relying more heavily on the results, as was the case for other oncologists. Our findings are similar to those of Spellman et al 28 , who found that oncologists were concerned that too much weight was given to test results rather than to other clinical data.…”
Section: Discussionsupporting
confidence: 81%
“…Qualitative studies with oncologists suggest they take a number of factors into consideration when ordering testing. These factors include not only clinical variables, but also patients’ pre-test preferences for chemotherapy 32 and the degree of uncertainty regarding their recommendation for chemotherapy. 33 Additional multi-method research is needed to further understand oncologists’ decision making processes about the use of GEP testing, and precision medicine more broadly, as well as how they involve patients in this process.…”
Section: Resultsmentioning
confidence: 99%
“…42,44 Explanation and discussion of intermediate risk are very challenging, and decisions are ultimately made by incorporating consideration of other clinical factors as well as patients' views and preferences. 44 Careful presentation of test results is important 42 because approximately one-third of patients have been found to not fully understand the test and its implications, 43 and there is some evidence that patients may overestimate the accuracy of the test. 46 • Other molecular prognostic tests that have been developed for predicting recurrence risk in early-stage breast cancer patients have also been evaluated in systematic reviews, 18,19 and recent studies have added to the evidence base for these tests.…”
Section: Contextual Issues Important To the Recommendationmentioning
confidence: 99%
“…Studies have begun to document how medical and surgical oncologists use the test, how they communicate results to patients, how well patients understand the information, and how they use it in decision making. [42][43][44][45] Although studies to date are too small to allow firm conclusions, their findings indicated that physicians generally assume the test has clinical utility and many use it as a primary tool in discussing risks and benefits of chemotherapy with women who have HR+ early breast cancer, often by directly sharing with them the report provided by Genomic Health. 42,44 Explanation and discussion of intermediate risk are very challenging, and decisions are ultimately made by incorporating consideration of other clinical factors as well as patients' views and preferences.…”
Section: Contextual Issues Important To the Recommendationmentioning
confidence: 99%
See 1 more Smart Citation